Bernard of Clairvaux : Sermons for Lent and the Easter Season - Bernard, of Clairvaux, Saint, 1090 or 1091-1153 (Book collections on Project MUSE., 2013)
This volume contains Saint Bernard's sermons for the liturgical seasons of Lent and Easter. Included are sermons for the Purification, Septuagesima, the feast of Saint Benedict, and the feast of the Annunciation, all of which are interpreted by Bernard in light of the paschal mystery. In the sermons for Lent, especially, one gets to know a more hesitant and searching Bernard than appears in his other liturgical sermons. This volume is the third of a projected five volumes of Bernard's liturgical sermons.